Manfaatkan Kotoran Sapi Menjadi Kompos Untuk Tanaman Masa Pandemi Di Kelurahan Umbansari Kota Pekanbaru - Latifa Siswati; Rini Nizar; Anto Ariyanto (Universitas Lancang Kuning, 2021)
Farming is currently carried out with organic farming, so compost is needed to replace chemical fertilizers. The use of fertilizers made from organic raw materials is highly recommended, because fertilizers made from compost can help help nutrients in the soil, besides compost can also be made from raw materials that are around our environment.. Using compost can help farmers save on production costs, because compost can be made from unused raw materials. For example, compost derived from cow dung, usually does not have a price and benefits, it turns out that it can be used as a raw material for making compost so that this utilization can reduce production costs that are usually incurred by farmers. The purpose of this service is to provide knowledge to partners that it turns out that the livestock waste they cultivate can be used as raw material for composting so that livestock waste in the form of cow dung can be overcome and can also help farmers reduce costs incurred for farming which is also they do. Compost made from cow dung is very helpful in soil fertility and can be seen directly by its benefits for plants and soil. Conclusion The use of cow dung into compost is to reduce livestock manure waste. This community service activity is concluded to have improved the participants' knowledge, understanding, and skills by an average of 81.25%